Village Government Accountability in Managing Village Finances (Empirical Study in Yawosi District, North Biak, Biak Numfor Regency) - Maylen K.P Kambuaya; Klara Wonar; Fadly Yizhar; Rian Noviani Solissa; Elend Fransiska (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the influence of clarity of budget targets, reporting systems and competencies of village apparatus on the accountability of village fund management. The population is 8 villages in Yawosi District, Biak Numfor Regency. The sample of this study amounted to 168 respondents using the purposive sampling method. The data analysis technique used is Structural Equation Modeling (SEM) Part Least Square (PLS). The results of this study show that the clarity of budget targets and the internal control system have a positive effect on the accountability of village financial management, while the financial accounting system and the competence of village officials have no effect on the accountability of village financial management.